LITERATURE: AN INTELLECTUAL DOCUMENT - Juliasih Juliasih (Soegijapranata Catholic University, 2010)
Uncle Tom Cabin is a manifestation of thoughts and feelings or a continuous effort in the writer thinking activities in a society in her era. She offered an example of an abstraction or essence from a dream or a situation in the future, a goal or a target that she struggles for through the writer's contemplation. She offered other alternatives of other thoughts on freedom. In her book, she argued and reflected her perception about life. Therefore, when Harriet wrote about slavery, it was the result of her reflection on humanity. Uncle Tom Cabin which was widely influential shows that through their works, directly or indirectly. writers, in general, have given contributions to the development of their nation. This contribution is that they place literature as an intellectual document of the nation. Essentially, a literature can also be regarded as an intellectual model.